EXPLORING CONSUMER ATTITUDES: THE INFLUENCE OF SOCIAL MEDIA MARKETING ON FAST-MOVING CONSUMER GOODS IN KOZHIKODE, KERALA (CAHIERS MAGELLANES-NS, 2024)
This study delves into the complex dynamics of consumer attitudes in the Fast-Moving Consumer Goods (FMCG) sector in Kozhikode, Kerala, with a specific focus on the influence of social media marketing. Against the backdrop of an evolving consumer landscape, characterized by the ubiquity of digital platforms, our investigation aims to uncover the nuanced factors shaping purchasing decisions. Kozhikode, with its diverse consumer base, serves as an intriguing microcosm for understanding the symbiotic relationship between social media and FMCG preferences. Through an in-depth analysis, this research provides insights into the fluid nature of consumer attitudes, shedding light on how social media interactions impact perceptions and choices. The findings aim to equip businesses in the FMCG sector with tailored strategies to effectively engage with consumers in Kozhikode, fostering stronger connections in this dynamic market.